Detection of herpes simplex infection in viral conjunctivitis using polymerase chain reaction- a pilot study - Alwi, Azma Azalina Ahmad; Hussein, Elias; Gopalakrishnan, V.; Ravichandran, M. (2005)
A study was performed to detect the viral conjunctivitis in HUSM caused by HSV using a PCR method. Seventy patients with viral conjunctivitis were examined; with clinical features identified and conjunctival scrapping taken from superior and inferior fornices of affected eye for PCR analysis. PCR was performed with primers obtained from a commercially available primer kit for HSV. The prevalence of viral conjunctivitis in HUSM caused by HSV infection, using PCR method, was 17.I % (95 % CI = 8.1, 26.0) which was higher than other reported studies. This is mainly due to the method used which is a highly sensitive and specific diagnostic test. Majority of HSV conjunctivitis patients presented with moderate follicular conjunctivitis with frequent corneal involvement which was similar to features of adenoviral conjunctivitis caused by Group D subgenera. The possible differentiating feature of adenoviral conjunctivitis was the unilaterality.